The Validity of E-Learning Chemistry Learning in SMA / MA Project Based Learning on Hydrocarbons Using the Flipped Classroom Approach in Class XI Senior High School - Eka Frima Asda; Effendi Effendi; Abel Maaruf; Hamdhan Fathony; Isra Hidayati (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
This research has been carried out until the validity stage by producing an e-learning based on Project Based Learning (PjBL) on Hydrocarbons by applying the flipped classroo m approach in the learning process. The type of research used is R&D (Research and Development), with a 4-D model consisting of: (1) define, (2) design, (3) develop, and (4) disseminate. The products produced from the study were validated by 1 Chemistry lecturer of Faculty of Mathematics and Natural Sciences UNP and 1 chemistry teacher at MAN 2 Pesisir Selatan, and continued at the revision stage based on input from the validator. The analysis of the validity test was carried out using the Cohen kappa formula. The mean Cohhen kappa results from construct and content validation were 0.811 and 0.844 with very high categories. Based on these results, the resulting e-Learning is valid and practice to use in the learning process.